The Rationality Of Malay Employees Working For Chinese Entrepreneurs - Yuhelna, Yuhelna; Isnaini, Isnaini; Elfemi, Nilda (Universitas PGRI Sumatera Barat, 2024)
This research aims to describe how the social relations of the Malay ethnic group work with Chinese ethnic entrepreneurs in Baran Barat Village, Meral District, Karimun Regency. The theory used is Max Weber's concept of social action. The approach taken is a qualitative approach with a descriptive type. Data collection techniques are purposive sampling and snowball sampling. The types of data are primary data and secondary data. Data collection techniques were carried out using document study, observation and in-depth interviews. Data analysis, data reduction, data presentation and drawing conclusions. The results of field research can be concluded that the rationality of the Malays working for Chinese entrepreneurs who worked for the Chinese ethnic group because of the job opportunities provided at that time, then the work given was in accordance with the abilities possessed and the results obtained by the workers were in accordance with the needs. There is a relationship of mutual need between Malay and Chinese ethnicities.